Stres dan Koping pada Pasien Dengan DM Tipe 2 dalam Pelaksanaan Manajemen Diet di Wilayah Puskesmas Banguntapan II Kabupaten Bantul - Andri Setyorini (STIKes Surya Global Yogyakarta, 2017)
Background: Type 2 DM is the most common case of all DM cases. The cause of type 2 diabetes in addition to genetic factors, can also occur due to the wrong diet, or lifestyle that is less healthy. So the patients must have a fairly strict diet. This can lead to burnout and stress because they have to obey the recommended diet plan during their lifetime. Therefore, the sufferer should always understand that stress is the trigger for the increase in blood glucose levels that should be controlled by proper coping (Rasmun, 2004). Objective: The purpose in this study was to look at the description of stress and coping in patients with type 2 DM in the implementation of diet management at the community health center Banguntapan II Bantul Yogyakarta. Research Methode: This research used descriptive qualitative approach which is done on natural setting (natural condition). Primary data sources and data collection techniques were more in depth interviews, observation and documentation. Analysis of the data used is qualitative content analysis. Determination of participants in this study was conducted with purposive sampling technique. Participants in this study are DM type 2 patients who are undergoing outpatient at Banguntapan II Community Health Centers in Bantul and has not happened chronic complications. The study involved 19 people participants.. Results: The results of this study indicate 3 main themes and 12 sub themes that related to the description of stress and coping in patients with type 2 diabetes in the implementation of diet management, there are: 1) Stress in Patient DM Type 2 that has 5 aspects that are related to early diagnosed DM patients, perceived complaints, long suffered DM, diet control, and other causes; 2) Management of Diet Program by Patient DM Type 2 which deals with 2 aspects, namely related to the regulation of the amount and type of food as well as the arrangement of the number and the schedule of the meal; and 3) Coping Stress in Implementing a DM Diet consisting of 5 aspects of therapy, diet modification, positive thinking, obedience to diet and dietary disobedience. Conclution: In general, this research indicate 3 main themes, there are: 1) Stress in Patients DM Type 2; 2) Management Diet Program by Patient DM Type 2; and 3) Coping stress in Implementing Diet.